Bishop von Galen : German Catholicism and National Socialism - Griech-Polelle, Beth A., 1964- (Yale University Press, 2002)
Clemens August Graf von Galen, Bishop of Münster from 1933 until his death in 1946, is renowned for his opposition to Nazism. This provocative revisionist biographical study views him from a different perspective: as a complex figure who moved between dissent and complicity during the Nazi regime.